Interaction of Bacterial Membrane Vesicles with Specific Species and Their Potential for Delivery to Target Cells - Tashiro, Yosuke; Hasegawa, Yusuke; Shintani, Masaki; Takaki, Kotaro; Ohkuma, Moriya; Kimbara, Kazuhide; Futamata, Hiroyuki (Frontiers in Microbiology, 2017)
Membrane vesicles (MVs) are secreted from a wide range of microbial species and transfer their content to other cells. Although MVs play critical roles in bacterial communication, whether MVs selectively interact with bacterial cells in microbial communities is unclear. In this study, we investigated the specificity of the MV-cell interactions and evaluated the potential of MVs to target bacterial cells for delivery. MV association with bacterial cells was examined using a fluorescent membrane dye to label MVs. MVs derived from the enterobacterium Buttiauxella agrestis specifically interacted with cells of the parent strain but interacted less specifically with those of other genera tested in this study. Electron microscopic analyses showed that MVs were not only attached on B. agrestis cells but also fused to them. The interaction energy, which was characterized by hydrodynamic diameter and zeta potential based on the Derjaguin-Landau-Verwey-Overbeek (DLVO) theory, was significant low between MVs and cells in B. agrestis, compared to those between B. agrestis MVs and cells of other genera. Similar specific interaction was also occurred between B. agrestis MVs and cells of six other species belonging to Buttiauxella spp. B. agrestis harboring plasmid pBBR1MCS-1 secreted plasmid-containing MVs (p-MVs), and plasmid DNA in p-MVs was transferred to the same species. Moreover, antibiotic-associated MVs enabled effective killing of target species; the survival rate of B. agrestis was lower than those of Escherichia coli and Pseudomonas aeruginosa in the presence of gentamicin-associated MVs derived from B. agrestis. Altogether, we provide the evidence that MVs selectively interact with target bacterial cells and offer a new avenue for controlling specific bacterial species using bacterial MVs in microbial communities.